(untitled) (Research, Society and Development, 2022)
Social isolation and alcohol use are cases of notification and therefore require continuous health surveillance since the risk of physical violence in women. To analyze social isolation and reports of physical violence in a Brazilian Northeast Region. Descriptive ecological study about reports of physical violence against women in Ceará. The collection of teaching data in the SINAN/DATASUS database, from 2016 to 2021 and 8,754 cases of physical violence in education were reported, with the profile of victims in the brown race 6,593, schooling: incomplete high school: 1944 .There was a predominance of alcohol consumption in the aggressor of violence in 3,714 cases. The notifications pointed to a significant decrease in the year 2021, implying the period of social isolation in the COVID-19 pandemic.